Prompt and Appropriate Antimicrobial Therapy Improves Outcomes of NDM-Producing and KPC-Producing Klebsiella pneumoniae Bloodstream Infections in Patients Hospitalized for COVID-19: A Comparative Retrospective Case-Series - Davide Fiore Bavaro; Alessandra Belati; Lucia Diella; Melita Anna Poli; Angela Calamo; Giovanna De Candia; Maurantonio Altamura; Felicia Anna Spadavecchia; Gaetano Brindicci; Nicolò De Gennaro; Francesco Di Gennaro; Annalisa Saracino; et al. (Antibiotics, 2022)
Secondary bloodstream infections (BSIs) caused by KPC- and NDM-producing Klebsiella pneumoniae (K.p.) during the course of COVID-19 infections lead to significant mortality. Herein, a comparative retrospective case series of KPC- or NDM-K.p. BSIs occurring in COVID-19 subjects treated with Ceftazidime/Avibactam (CAZ/AVI) for KPC-K.p., or CAZ/AVI+ Aztreonam (ATM) for NDM-K.p is reported. All patients hospitalized for COVID-19 in two Italian hospitals with a BSI between March and September 2021 were included. The main outcome was 14-day mortality. Overall, 44 patients were included: 23 with KPC-K.p. and 21 with NDM-K.p. BSIs. The median (q1–q3) age was 67 (57–75) years, and 32 (72%) were males. The two groups were similar in terms of baseline comorbidity, or severity of COVID-19. Notably, 14-day mortality of KPC-K.p. BSIs and NDM-K.p. BSIs (26% vs. 38%, p = 0.521) and 28-day mortality (35% vs. 48%, p = 0.541) were similar. A Cox regression model of delayed initiation of an appropriate antibiotic therapy after the onset of symptoms independently predicted mortality: initiation between 24 and 72 h (aHR = 12.03; 95% CI = 1.10–130, p = 0.041); and initiation after 72h (aHR = 36.9, 95% CI = 3.22–424, p = 0.004). Moreover, a trend towards an increased risk of mortality was observed for polymicrobial infections (aHR = 3.73, 95% CI = 0.87–15.8, p = 0.074), while a protective effect was observed for a beta-lactam loading dose at the start of treatment (aHR = 0.16, 95% CI = 0.02–1.10, p = 0.064). The high mortality of KPC and NDM-K.p. BSIs in COVID-19 patients may be reduced by an early and appropriate antibiotic therapy. Further efforts should be made to develop antimicrobial stewardship and infection control programs in COVID-19 wards.